Sensory acceptability of an infusion of Hibiscus rosa-sinensis, Mentha piperita L. and Citrus sinensis peel (LACCEI, 2024)
The objective of this investigation was to determine the treatment with the highest sensory acceptability of a filtering infusion based on Hibiscus rosa-sinensis, Mentha piperita L and Citrus sinensis peel. This research is of an applied type of experimental design, an untrained panel of 30 people over 18 years of age from the Trujillo district was used. A sensory evaluation sheet with a hedonic scale from 0 to 5 was applied as an instrument, which raised 4 treatments with different percentages of raw materials, as a result it was determined that treatment 3 with 28.5% cayenne flower, 52% of mint and 19.5% of orange peel obtained greater acceptability and complies with the physicochemical requirements with a humidity of 11.02%, pH 7.4 and ashes with 7.11%. Likewise, the microbiological results met the limits established for an infusion with 9x102 CFU/g for Enterobacteriaceae and 7x102 CFU/g for molds, being suitable for consumption. Finally, it was concluded that in the evaluation of sensory acceptability, T3 was the most acceptable with a value of 4.8 considering that the taste had a higher preference with an average of 4.70, followed by smell with 4.66, color with 4.46 and appearance with 4.43.